Skeletal muscle dysfunctions in pulmonary arterial hypertension: Effects of aerobic exercise training - Drummond, Filipe Rios; Leite, Luciano Bernardes; de Miranda, Denise Coutinho; Drummond, Lucas Rios; Lavorato, Victor Neiva; Soares, Leôncio Lopes; Neves, Clóvis Andrade; Natali, Antônio José (Frontiers in Physiology, 2023)
Pulmonary arterial hypertension is associated with skeletal muscle myopathy and atrophy and impaired exercise tolerance. Aerobic exercise training has been recommended as a non-pharmacological therapy for deleterious effects imposed by pulmonary arterial hypertension. Aerobic physical training induces skeletal muscle adaptations via reduced inflammation, improved anabolic processes, decreased hypoxia and regulation of mitochondrial function. These benefits improve physical exertion tolerance and quality of life in patients with pulmonary arterial hypertension. However, the mechanisms underlying the therapeutic potential of aerobic exercise to skeletal muscle disfunctions in patients with pulmonary arterial hypertension are not well understood yet. This minireview highlights the pathways involved in skeletal muscle adaptations to aerobic exercise training in patients with pulmonary arterial hypertension.